2020
DOI: 10.1109/access.2020.3019350
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis on Perceptual Contrast and Its Use in Visual Information Analysis and Processing

Abstract: Contrast in visible images is one of the most relevant characteristics of visual signals. Since the pioneering works performed in vision psychology and optics, different definitions have been proposed in the literature. However, for the time being there exist no definition of contrast on which the vision research and visual processing scientific community can agree on. This makes it critical to have a clear view on the notion of contrast and its use in various applications. One issue to consider is how to defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 159 publications
0
8
0
Order By: Relevance
“…Defocus-Blur: A video may suffer from blur due to defocus during the image capture. This results in a decrease of the image contrast [13] that manifests itself as sharpness decreases. The blur due to defocus can be generated at various levels by applying a low-pass Gaussian filter to the input image with a variable mask size relates to the standard deviation of the impulse response of the filter.…”
Section: Artificial Distortionsmentioning
confidence: 99%
“…Defocus-Blur: A video may suffer from blur due to defocus during the image capture. This results in a decrease of the image contrast [13] that manifests itself as sharpness decreases. The blur due to defocus can be generated at various levels by applying a low-pass Gaussian filter to the input image with a variable mask size relates to the standard deviation of the impulse response of the filter.…”
Section: Artificial Distortionsmentioning
confidence: 99%
“…In this work, we focus on contrast, a specific image attribute that not only influences the perception of image quality [14] but also causes one of the largest variabilities among observers when used as a type of distortion in testing image quality preferences [1]. Exploring this particular attribute, our objective is to identify distinctive observer preferences in order to use this information to improve personalized image quality in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast is often measured using different mathematical measures and metrics [14], such as the Michelson contrast [24], RMS contrast, Weber contrast [25], Local contrast [26], and contrast-to-noise ratio [27]. However, these metrics are less susceptible to individual preferences as they are based on objective measures of image contrast rather than subjective perception.…”
Section: Introductionmentioning
confidence: 99%
“…Lami et al [27] introduced a system to quantify the vision through a polymer-dispersed liquid crystal double-glazed window in commercial buildings. The study concluded that it is possible to quantify the vision through windows glazing in terms of image contrast [28,29]. The experimental part of the study included the procedures of vision quantification process.…”
Section: Introductionmentioning
confidence: 99%